Ideology and development in Africa - Young, Crawford, 1931-; Council on Foreign Relations (New Haven : Yale University Press, 1982)
Monographic comparison of political ideology and foreign policy on economic development performance in Africa - examines the emergence of socialism in historical perspective, the economic growth of countries with capitalist political systems, and proceeds with an evaluation of income distribution, the preservation of human rights in planned economies and market economies, etc. References.
Ideology and development choice -- The rise of the Afro-Marxist regime -- The populist socialist pathway -- The African capitalist state -- African ideological preference and great power relations -- A preliminary appraisal of ideology and performance
"Council on Foreign Relations books."
Includes bibliographical references and index.
Keywords: Since 1960; Geschichte 1960-1980; Africa; ideologies; development; 89.40 internal relations of the state: general; 2; 2; 2; Economic history; Politics and government; Social conditions; Ideologie; 2; Wirtschaftsentwicklung; Politik; Politisches System; Wirtschaftssystem; Kommunismus; Politieke situatie; Sociaal-economische ontwikkeling; political ideology; foreign policy; economic development; socialism; history; economic growth; capitalist; political system; evaluation; income distribution; human rights; planned economy; market economy; Africa; Ideology; 2; 2; 2; socialisme; histoire; 2; capitaliste; 2; 2; 2; droits de l'homme.; 2; 2; 2; 2; 2; socialismo; historia; 2; capitalista; 2; 2; 2; derechos humanos